Hello studentUnion!
![\huge \boxed{\mathfrak{Question} \downarrow}](https://img.qammunity.org/2022/formulas/business/college/w7rd9ddf5swaqx6h7w2rdc7fe2s24fsc06.png)
Solve the equation-
![(5)/(x - 3) - (4)/(x + 4) = (1)/(x) \\](https://img.qammunity.org/2022/formulas/mathematics/high-school/btb6iqg25i4buf59hite3st669zxw93t7o.png)
![\large \boxed{\mathfrak{Answer \: with \: Explanation} \downarrow}](https://img.qammunity.org/2022/formulas/business/college/6rihqyi13zmt3iigtmkd6hstdpaj7k3civ.png)
![(5)/(x - 3) - (4)/(x + 4) = (1)/(x) \\](https://img.qammunity.org/2022/formulas/mathematics/high-school/btb6iqg25i4buf59hite3st669zxw93t7o.png)
Let's multiply both the sides of the equation by x (x - 3) & (x + 4) which is the LCM of (x - 3), (x + 4) & x. We can't solve it directly without taking the LCM first as the denominators are not equal to each other. Then do cross multiplication. After all these steps, you'll get an equation as..
![x\left(x+4\right)* 5-x\left(x-3\right)* 4=\left(x-3\right)\left(x+4\right) \\](https://img.qammunity.org/2022/formulas/mathematics/high-school/iccmc2q2p4yz3htb0pxc9rxu3simwy4xc5.png)
Now, use the distributive property & simplify it.
![x\left(x+4\right)* 5-x\left(x-3\right)* 4=\left(x-3\right)\left(x+4\right) \\ \left(x^(2)+4x\right)* 5-x\left(x-3\right)* 4=\left(x-3\right)\left(x+4\right) \\ 5x^(2)+20x-x\left(x-3\right)* 4=\left(x-3\right)\left(x+4\right) \\ 5x^(2)+20x-\left(x^(2)-3x\right)* 4=\left(x-3\right)\left(x+4\right) \\ 5x^(2)+20x-\left(4x^(2)-12x\right)=\left(x-3\right)\left(x+4\right) \\ 5x^(2)+20x-4x^(2)+12x=\left(x-3\right)\left(x+4\right) \\ x^(2)+20x+12x=\left(x-3\right)\left(x+4\right) \\ x^(2)+32x=\left(x-3\right)\left(x+4\right) \\ x^(2)+32x=x^(2)+x-12 \\ x^(2)+32x-x^(2)=x-12 \\ 32x=x-12 \\ 32x-x=-12 \\ 31x=-12 \\ \boxed{ \boxed{ \bf \: x=-(12)/(31) }}](https://img.qammunity.org/2022/formulas/mathematics/high-school/6e5tovvdpqxmsw7ocjy3wcgffgaduscwad.png)
- The value of x is -12/31.
__________________
Hope it'll help you!
ℓu¢αzz ッ